Societal religiosity for commercial and social entrepreneurship - Muralidharan, Etayankara; Pathak, Saurav (My University, 2025)
Our study, using 23,395 individual observations from the Global Entrepreneurship Monitor survey from 18 countries and supplemented with data on societal religiosity from the Gallup Survey, demonstrates that the influence of societal affective religiosity on the likelihood of individual-level engagement in commercial entrepreneurship (CE) and social entrepreneurship (SE), is contingent on a country’s cultural and socioeconomic conditions. Societal in-group collectivism and performance orientation both moderate positively the influence of affective religiosity on CE and SE. Furthermore, while societal income mobility moderates negatively the influence of affective religiosity on CE and SE, societal income inequality positively moderates the influence of affective religiosity on only SE. Our findings establish cultural and socio-economic conditions as contexts for the effects of affective religiosity on CE and SE to be realized in society.
Presented July 25-29, 2025 at the 85th Academy of Management Annual Meeting, in Copenhagen, Denmark.
Keywords: Global Entrepreneurship Monitor; society; affective religiosity; socio-economic conditions